Consumers' Perception About Front of Package Food Labels (FOPL) in India: A Survey of 14 States - Sudip Bhattacharya; Om Prakash Bera; Vandana Shah (Frontiers Media S.A., 2022)
IntroductionFront of Package Food Labels (FoP) help consumers make healthier food choices at the point of purchase by giving details about the nutrients available in the packaged food items.Aim and ObjectiveA prospective multi-centric cross-sectional study was conducted in 2021 across India to evaluate the existing knowledge and attitude regarding food labels on packaged foods and beverages. Also, the objective understanding of the consumers' knowledge on different types of FoP label practiced across the world was determined.MethodologyA self-administered questionnaire was given to the respondents to gather their attitudes regarding the FoP label. Besides, they were given colored pictures of different FoP labels to seek their perception and preference for different FoP label designs.ResultsResults found that packaged food and beverages were consumed by 91.3% of the participants. Awareness about the food package labeling was widely held by 95% of the participants and 88.6% of them considered this information helpful. Over half (55.4%) of the respondents considered packaged foods as healthy. Warning Labels (WL) were the most preferred food labels (93%), followed by Multiple Traffic Lights (MTL) and the difference between the two was statistically significant (p-value < 0.05).ConclusionsThe awareness about FoP labels is low among the consumers.RecommendationsEvidence-based research is recommended regarding the knowledge and perception of people on the feasibility of FoP label design which may lay a foundation to formulate laws and policies regarding the front of pack labeling.